RESISTANCE AND RESILIENCE: THE EVOLUTION OF FEMINIST VOICES IN INDIAN ENGLISH WOMEN’S POETRY - Vatsala; Kamboj, Kiran; Pant, Girish (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Indian English women’s poetry has undergone a significant transformation over the decades, evolving as a powerful medium for resistance and resilience against socio-cultural and patriarchal constraints. This paper explores the evolution of feminist voices in Indian English poetry, focusing on how women poets have navigated gender dynamics, tradition, and modernity to articulate their personal and collective experiences. By analyzing the works of key poets such as Kamala Das, Imtiaz Dharker, Meena Kandasamy, and Eunice de Souza, this study examines how womanhood, identity, and agency are redefined in their poetry. These poets challenge stereotypical portrayals of women, reclaiming narratives through themes of sexuality, autonomy, and subversion of patriarchal norms. The present paper is an honest attempt to attract the attention of the readers towards Resistance and Resilience: The Evolution of Feminist Voices in Indian English Women’s Poetry which refers to the defiance against oppressive social structures, while resilience denotes the strength and perseverance of women in overcoming adversities. The research scholar further writes that the present paper also delves into how Indian women poets engage with mythology, folklore, and history to critique dominant socio-religious structures while simultaneously drawing strength from Indic traditions. The reimagining of female mythological figures such as Sita, Draupadi, and Radha serves as an act of literary rebellion, reshaping these narratives from a feminist lens. The role of all the poets is very appreciable.